Exploring the Teachers’ Attitude Towards Inclusive Education at Elementary Level - Subhrajyoti, Trupti; Acharya, Amulya Kumar (THE PRIMARY TEACHER, 2025)
Inclusive Education (IE) aims to provide equal learning opportunities for all students, regardless of their diverse abilities and backgrounds. With the growing recognition of the importance of inclusive education, the National Education Policy 2020 document mentioned that “the education system must aim to benefit India’s children, so that no child loses any opportunity to learn and excel because of circumstances of birth or background”. Therefore, each and every educational development programme shall focus on bridging gaps in access, participation and learning outcomes in school education, where the role and functions of a teacher, particularly at the elementary level, can never be ignored. The present study aims to examine the attitude of elementary school teachers towards inclusive education at the elementary level. A sample of 50 elementary teachers appointed in both rural and urban areas of Balasore district, Odisha were selected through simple random sampling techniques from 10 institutions. Researchers used the ‘Teacher Attitude Scale Towards Inclusive Education’—a standardised tool developed by Vishal Sood and Arti Anand in 2011 for data collection. Collected data were statistically analysed by using percentage, mean, SD and t-test. The result showed that elementary teachers had 67.74 per cent favourable attitude towards inclusive education. Further, it particularly showed that teachers had 28.86 per cent of unfavourable attitude with respect to psychological/behavioural aspects, 29.74 per cent of favourable attitude with respect to social and parent-related aspect, 26.84 per cent of unfavourable attitude with respect to administrative aspects, and no major differences were found in the percentage of favourable and unfavourable attitude of elementary teachers with respect to the curricular and co-curricular aspects of inclusive education. Moreover, the elementary level teachers appointed both in rural and urban area schools had the same attitude with regard to inclusive education.